2015
DOI: 10.1111/ejh.12609
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine in multiple myeloma

Abstract: The advent of high-dose melphalan with autologous stem-cell transplantation (ASCT), the availability of novel agents such as thalidomide, lenalidomide (immunomodulatory drugs or IMiDs) and bortezomib (proteasome inhibitor) and improvements in supportive care have allowed to increase overall survival in multiple myeloma (MM) patients; nevertheless, MM remains an incurable pathology. For this reason, newer agents are required for continued disease control. Bendamustine is an old drug rediscovered in the last dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
0
16
1
1
Order By: Relevance
“…Chemotherapeutic alkylating agents are known to cause bone marrow toxicity and myelosuppression through cell death of hematopoietic precursors and differentiated mature bone marrow cells. 51 , 52 , 53 Moreover, we have previously shown that mouse bone marrow is highly sensitive to alkylation-induced cytotoxicity. 48 , 49 , 54 , 55 Indeed, we observed that bone marrow cellularity in WT or Alkbh7 −/− mice was decreased as early as 2 h after MMS treatment with continuing depletion of red blood cells, megakaryocytes and myeloid precursors throughout the MMS exposure period (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapeutic alkylating agents are known to cause bone marrow toxicity and myelosuppression through cell death of hematopoietic precursors and differentiated mature bone marrow cells. 51 , 52 , 53 Moreover, we have previously shown that mouse bone marrow is highly sensitive to alkylation-induced cytotoxicity. 48 , 49 , 54 , 55 Indeed, we observed that bone marrow cellularity in WT or Alkbh7 −/− mice was decreased as early as 2 h after MMS treatment with continuing depletion of red blood cells, megakaryocytes and myeloid precursors throughout the MMS exposure period (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Bendamustine is a well-known alkylating agent initially developed in the 1960s, which has more recently been under increasing investigation for its potential utility in the treatment of MM [ 88 ]. Bendamustine acts as a classical alkylating agent of the nitrogen mustard class by inducing cell cycle arrest and promoting apoptosis via the alkylation of DNA [ 88 ].…”
Section: Novel Agentsmentioning
confidence: 99%
“…Bendamustine is a well-known alkylating agent initially developed in the 1960s, which has more recently been under increasing investigation for its potential utility in the treatment of MM [ 88 ]. Bendamustine acts as a classical alkylating agent of the nitrogen mustard class by inducing cell cycle arrest and promoting apoptosis via the alkylation of DNA [ 88 ]. Recent trials have demonstrated the efficacy of bendamustine, in combined regimens, among broader cohorts of myeloma patients, and in particular among those with relapsed and/or refractory disease [ 89 ].…”
Section: Novel Agentsmentioning
confidence: 99%
“…Bendamustine is a well-tolerated agent with a double mechanism of action, alkylating and antimetabolite, with proved effectiveness in treatment of relapsed/refractory [10, 11] and newly diagnosed multiple myeloma [12, 13] and in a relapsing/refractory setting [1419]. In rrMM it can be used as single agent combined to dexamethasone, but a synergistic effect has been demonstrated when associated with bortezomib.…”
Section: Discussionmentioning
confidence: 99%